Parenti, C. (2012). Tropic of Chaos. Climate change and the new geography of violence - Saurí i Pujol, David (Documents d’Anàlisi Geogràfica, 2014)
PARENTI, C. (2012) Tropic of Chaos. Climate change and the new geography of violence New York: Nation Book, X+ 295 p. ISBN 978-1-568858-729-5 (paperback)